Theorising Widowhood: Feminist Philosophical Perspectives on Widowhood Practices and the Politics of Inheritance in Southeastern Nigeria - Mary Julius Egbai (Universitas Negeri Makassar, 2026)
Widowhood practices in many African societies, including mourning rituals, property inheritance, and levirate marriage, have been the subject of extensive feminist critique. These practices have been condemned as patriarchal, oppressive, and in violation of women’s rights. However, the feminist philosophical literature on widowhood has often been framed in terms of a binary opposition between tradition and modernity, with tradition coded as oppressive and modernity as liberating. This paper argues that this binary is inadequate for understanding the moral complexity of widowhood practices. Drawing on the work of African feminist philosophers and on ethnographic studies of widowhood in southeastern Nigeria, the paper develops a nuanced analysis of widowhood that recognises both the genuine harms that some practices inflict and the ways in which widowhood can also be a site of women’s agency, solidarity, and resistance. It proposes a contextual feminist approach that evaluates widowhood practices not against an abstract standard of individual autonomy but against the concrete conditions of women’s lives. The paper contributes to feminist philosophy by demonstrating the need for culturally situated analyses of gender oppression that attend to the specific institutions, practices, and beliefs that shape women’s experiences.